2017
DOI: 10.1080/07434618.2017.1301550
|View full text |Cite
|
Sign up to set email alerts
|

Beliefs and habits: staff experiences with key word signing in special schools and group residential homes

Abstract: Even though use of aided augmentative and alternative communication (AAC) by staff has been extensively researched, few studies relate to unaided AAC strategies such as key word signing (KWS). We explored the KWS views of two groups: direct support staff in group residential homes and teachers from special education secondary schools. We examined transcripts from individual semi-structured interviews with five direct support staff and five teachers using thematic analysis. Participants discussed consistency of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 46 publications
(67 reference statements)
1
29
0
Order By: Relevance
“…In a recent qualitative study, Rombouts, Maes, and Zink () interviewed teachers about their beliefs and habits in using KWS. Teaching staff reported that their signing skills deteriorated quickly if they did not regularly use KWS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent qualitative study, Rombouts, Maes, and Zink () interviewed teachers about their beliefs and habits in using KWS. Teaching staff reported that their signing skills deteriorated quickly if they did not regularly use KWS.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent qualitative study, Rombouts, Maes, and Zink (2017) interviewed teachers about their beliefs and habits in using KWS.…”
Section: Introductionmentioning
confidence: 99%
“…The consistency with which staff use KWS may vary between settings. In an interview study, one direct support staff person and one teacher felt that KWS was used less in services for adults than in special schools (Rombouts et al, ). Other studies seem to support this.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we observed how teachers and direct support staff used KWS during various group activities. First, we hypothesised that staff used KWS more consistently in schools than in day centres for adults (Rombouts et al, ). Second, we expected that staff used KWS more during structured activities with a direct focus on KWS than during activities without such focus (Grove & McDougall, ; Norburn et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation